تأثير معوقات التسويق عبر الإنترنت على نية الشراء الإلكتروني "دراسة ميدانية على طلاب الكليات في طرطوس" - ديوب, محمد عباس; خضر, لورين (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدف البحث إلى التعرف على العوامل التي تعيق استخدام التسويق عبر الإنترنت من قبل الأفراد, تم الاعتماد على المنهج الوصفي، وتم تطوير استبانة والتأكد من صدقها ومعامل ثباتها، وتم توزيع الاستبيان على طلاب كلية الاقتصاد الثانية في طرطوس وذلك للحصول على البيانات اللازمة لإجراء الدراسة.توصل البحث إلى النتائج الآتية: لا توجد علاقة ذات دلالة إحصائية بين (البنية التحتية للإنترنت، المخاطر المتوقعة، عدم الثقة بالتسويق عبر الإنترنت، التشريعات والقوانين) وبين النية في الشراء الإلكتروني، بينما توجد علاقة ذات دلالة إحصائية بين ضعف الخبرة والوعي بالتسويق عبر الإنترنت والنية في الشراء الإلكتروني وهذه النتائج تعود إلى طبيعة العينة المأخوذة. قدم البحث مجموعة من التوصيات أهمها: ضرورة نشر الوعي والثقة والمعرفة العلمية بأهمية التسويق عبر الإنترنت، والحاجة إلى زيادة الوعي بأهمية استخدام الحاسب.The objective of this research is to identify the obstacles to the use of internet marketing by individuals, has been relying on descriptive analytical method, a questionnaire was developed and make sure of his sincerity and the persistence coefficient, the questionnaire was distributed to the students of the Faculty the second of Economy in Tartous, in order to obtain necessary data for the study.The study found the following results: There were no statistically significant differences between (the Internet infrastructure, the expected risk, distrust for electronic marketing, legislation and laws) and the faith in e-procurement, while no statistically significant relationship between the weakness of experience and awareness of internet marketing and intent in e-procurement and these results back to the nature of the sample taken.The study was presented a set of recommendations including: the need to raise awareness of and confidence in scientific knowledge about the importance of internet marketing, and the need to increase awareness of the importance of the use of computer.